High yield of second-generation ethanol in an ionic Liquid-Cellulase integrated system for single-step processing of empty fruit bunch - Elgharbawy, A.A.M. (Taylor and Francis Ltd., 2021)
Ionic liquids (ILs) are regarded as green solvents and have demonstrated ability in the solvation of lignocellulosic material, thus promoting its enzymatic hydrolysis by cellulases. In this study, cellulase (PKC-Cel) obtained from Trichoderma reesei (RUTC30) through fermentation displayed good stability in choline acetate ChoOAc, a biodegradable IL. Empty fruit bunches (EFB) were subjected to single-step hydrolysis in an IL-enzyme system. Response surface methodology was employed to maximize ethanol production. Three parameters were optimized, namely sugar loading, inoculum concentration, and agitation. The distilled ethanol purity was 98.6% (v/v). The ethanol yield was 87.94% of the theoretical yield, which was 0.275 g ethanol gâ1 EFB. In comparison, the non-IL system produced 0.127 g gâ1 EFB. The yield coefficients (Formula presented.), (Formula presented.), and (Formula presented.) were 0.552, 0.148, and 3.69 g gâ1. The specific growth rate (Formula presented.) was determined to be 0.264 hâ1 and the (Formula presented.) was 0.777 hâ1. Â© 2019 Informa UK Limited, trading as Taylor & Francis Group.